(untitled) - Thompson, Robert (Lanham, Maryland, 2004)
The Broadcast Journalism Handbook has everything you ever wanted to know about working in the television news business but were afraid to ask! Learn the ropes--and how to head off amateur errors--from the authors' vast experiences and dozens of interviews with news professionals. Complete with job-searching tips, helpful web sites, and real-life scenarios, this book covers many newsroom positions, from assignment editors to producers, reporters, and anchors. It gives you newsroom experience before you get the job
Keywords: Television broadcasting of news,Broadcast journalism; Vocational guidance,Vocational guidance